1988
DOI: 10.1097/00003086-198807000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Total Posterior Vertebrectomy of the Thoracic or Lumbar Spine

Abstract: A total vertebrectomy in the thoracic or lumbar spine via a posterior approach can provide optimal neural decompression in certain severely compromised terminal patients affected with a malignant metastatic spinal lesion. The Arbeitsgemeinschaft fur Osteosynthesefragen (AO) internal fixator, accompanied by methyl methacrylate reconstruction of the anterior vertebral column, provides sufficient stabilization so that immediate ambulation with minimal external support is possible. This single operative procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 1 publication
1
55
0
Order By: Relevance
“…If anterior instrumentation is not sufficient (e.g., in tumor cases) or not desired (e.g., in spondylitis), combining it with posterior pedicular fixation allows a very solid construct and permits limiting the instrumentation to only the involved levels [34,117]. In palliative tumor surgery, pedicular stabilization permits posterior tumor decompression and debulking with regard to restoration or prevention of paraplegia [77,114]. Thus, anterior surgery, which is often ill-advised in these patients, can be avoided.…”
Section: Tumors and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…If anterior instrumentation is not sufficient (e.g., in tumor cases) or not desired (e.g., in spondylitis), combining it with posterior pedicular fixation allows a very solid construct and permits limiting the instrumentation to only the involved levels [34,117]. In palliative tumor surgery, pedicular stabilization permits posterior tumor decompression and debulking with regard to restoration or prevention of paraplegia [77,114]. Thus, anterior surgery, which is often ill-advised in these patients, can be avoided.…”
Section: Tumors and Infectionmentioning
confidence: 99%
“…Magerl and Coscia [114] described a technique for a total posterior vertebrectomy in the thoracolumbar spine for metastasis. After the vertebrectomy, the spinal column is reconstructed with a methyl-methacrylate buttress for the anterior column and an angle-stable, rigid fixation with the AO internal fixator.…”
Section: Tumors and Infectionmentioning
confidence: 99%
“…As an alternative treatment, en bloc spondylectomy of spinal malignancies has attracted growing interest. It circumvents direct exposure of the tumor tissue and enables the surgeon to reach wide resection margins of the spine [8,18,20,32,35,46,48,51,52,[58][59][60]70]. For selected patients, the en bloc resection is expected to decrease local recurrence rates and improve the patient's chances of overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, intralesional surgery predisposes the patient to local recurrences and poor prognosis. To reduce the surgery-induced tumor cell dissemination, decrease local recurrence rates and to improve survival times, different techniques [8,15,16,20,23,25,26,32] for wide resections at the spine, involving either en bloc total [32] or hemilaminectomy [18] followed by en bloc corporectomy and dorso-ventral stabilization have been developed. In early 1980, Stener and Roy-Camille were the first to describe en bloc spondylectomy via a posterior approach after complete resection of the dorsal vertebral structures, i.e., both laminae, spinous process and parts of the pedicles, resulting in an oncological adequate resection for primary bone tumor locations not extending beyond the vertebral body [23,26].…”
Section: Introductionmentioning
confidence: 99%
“…In early 1980, Stener and Roy-Camille were the first to describe en bloc spondylectomy via a posterior approach after complete resection of the dorsal vertebral structures, i.e., both laminae, spinous process and parts of the pedicles, resulting in an oncological adequate resection for primary bone tumor locations not extending beyond the vertebral body [23,26]. Based on these reports, several authors have begun to develop further techniques for en bloc vertebrectomy encompassing variable indications, approaches, stabilization techniques and yielding promising results in view of local control and overall prognosis [6,20,27,32,38]. Tomita et al reported a technique with dorsal en bloc resection after transpedicular osteotomy followed by ventral vertebrectomy [32].…”
Section: Introductionmentioning
confidence: 99%